2005
DOI: 10.1111/j.1365-2249.2005.02903.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of T cells from women with antibodies to the human platelet antigen (HPA)-1a to peptides encompassing the HPA-1 polymorphism

Abstract: SummaryThe human platelet antigen-1a (HPA-1a) is the most common alloantigenic target in fetal and neonatal alloimmune thrombocytopenia (NAIT). Treatment currently depends on the outcome in previous pregnancies. HPA-1 specific T cell responses were determined in 14 HPA-1a alloimmunized women during or after pregnancies affected by NAIT. Peripheral blood mononuclear cells were incubated with peptides encompassing the Leu33Pro polymorphism (residues 20-39 and 24-45 in both Leu33 (HPA-1a) and Pro33 (HPA1b) forms)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 46 publications
(69 reference statements)
4
26
0
Order By: Relevance
“…Previous reports have provided considerable support to the notion that HPA-1a-specific T cells are present in [17][18][19] In the study published by Maslanka et al, 18 the investigators used TCR spectratyping and PCR techniques with clonotypic primers to track T cells growing in these cultures stimulated with a peptide containing the HPA-1a epitope. The clonotypic primers were also used to show the presence of these T cells in PBMCs at various time points in relation to pregnancy and in platelet-stimulated cultures.…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports have provided considerable support to the notion that HPA-1a-specific T cells are present in [17][18][19] In the study published by Maslanka et al, 18 the investigators used TCR spectratyping and PCR techniques with clonotypic primers to track T cells growing in these cultures stimulated with a peptide containing the HPA-1a epitope. The clonotypic primers were also used to show the presence of these T cells in PBMCs at various time points in relation to pregnancy and in platelet-stimulated cultures.…”
Section: Discussionmentioning
confidence: 98%
“…HLA-DR52a was significantly overrepresented in these alloimmunized responders (3), but T cells were not cloned. Jackson et al have recently shown responses to HPA-1a peptides 24 -45 and 20 -39 in bulk PBMC cultures in 21% of alloimmunized mothers, but also to the 1b peptide or the 1a and the 1b peptides simultaneously (34).…”
Section: Detecting Specific T Cells In Fmait Mothersmentioning
confidence: 99%
“…8 Human platelet antigen (HPA) is located on cell membrane glycoproteins, and HPA-1 antigen is most commonly affected with FNAIT (80%). [10][11][12][13] It has been reported that maternal T cell clones associated with FNAIT recognize an integrin beta-3 epitope, which is anchored to the HLA-DRB3 *0101-encoded MHC molecule DR52a. A woman with antigen negative (HPA 1b/1b) is at risk when she has a partner with antigen positive either homozygous (HPA 1a/1a) or heterozygous (HPA 1a/1b).…”
Section: Introductionmentioning
confidence: 99%